The System Approach for Entrepreneurship-Based School Management in Vocational High Schools - Kisno Kisno; Sri Milfayetty; Nathanael Sitanggang; Mohammad Joharis Lubis (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study attempts to explore the system approach in school entrepreneurship management in Vocational High Schools (VHS). Although the government has made attempts to promote entrepreneurship, little progress has been made. Thus, it is possible to observe how the approach of running educational institutions with the idea of entrepreneurship is encouraging for schools and students to make the most of their potential. This qualitative study included five Vocational High Schools implementing the entrepreneurship-based school program and the data was collected via documentation. The data analysis activity was carried out throughout the research activity, and the most core activities include data simplification, data display and conclusions drawing. This study revealed that the system approach of developing school entrepreneurship in Vocational High Schools included the preparation stage (P), the planning stage (P), implementation stage (I), and the marketing stage (M). In order to develop an entrepreneurship-based school, the school must overcome a number of challenges, including external partners issues, funding issues, human resources issues, infrastructure issues, marketing issues, and momentum issues.